Biopsychosocial insights for the identification of sports talents: A scoping review - Lozada-Medina, Jesús L.; Hoyos-Espitia, Carlos A.; Cortina-Nuñez, Manuel de J.; Buelvas-Girón, Harry J.; Ossa, Cesar Argumedos de la; Ruiz-Escorcia, Rafael R. (Edelweiss Applied Science and Technology, 2025)
This review aims to identify the processes, concepts, and order of studies on the identification of sporting talent, to interpret them critically, and to generate a proposal for a sports talent identification system (STIS) that is flexible and adaptable to different contexts and ages. The studied population consisted of children and young people. The concept focused on talent identification systems within the sports context across various locations. The study was registered on the Open Science Framework (OSF). Searches were conducted in indexed databases and search engines utilizing AI. For the study selection process, the protocol called Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) was applied, using the COVIDENCE systematic review tool. A total of 58 papers were selected, primarily original studies and reviews, with 47 considering biomedical and physiological aspects, 19 psychological, and 19 environmental and sociocultural components. Geographically, most of the works were developed in Europe, North America, and Asia. An effective STIS should be a continuous and cyclical process, considering physical and anthropometric characteristics, maturational status, and psychosocial aspects. Utilizing easy-to-apply batteries will facilitate the identification, database creation, monitoring, and performance follow-up of sports talents efficiently.